Estimating the Epidemiology and Quantifying the Damages of Parental Separation in Children and Adolescents - Seijo, Dolores; Fariña, Francisca; Corras, Tania; Novo, Mercedes; Arce, Ramon (Frontiers in Psychology, 2016)
Parental separation is linked to multiple negative outcomes for children in all spheres of life. A field study was designed to estimate the epidemiology and to quantify the outcomes on the wellbeing of children from separated parents. Thus, data on socio-economic status, psychological adjustment, behavioural disorders, social relations, self-concept, and academic achievement were gathered from 346 children and adolescents, 173 separated parents, and 173 parents from intact families in the paediatric catchment area of Galicia (Spain). The results showed that parental separation had a significant negative impact on the children’s and adolescents’ family income (increasing the probability of falling below the poverty line); psychological adjustment (i.e., higher scores in anxiety, depression, hostility, paranoid ideation and interpersonal alienation); social relations (i.e., less self-control in social relations; higher social withdrawal); self-concept (lower levels of academic, emotional, physical and family self-concept), and academic achievement (lower academic achievement with higher school dropout rates). Moreover, children from separated families had a higher probability of being exposed to gender violence. Epidemiologically, parental separation is associated to the probability of falling below the poverty line 33.9%; being exposed to gender violence 43.2%; and symptoms such as depression, anxiety, hostility, paranoid ideation interpersonal alienation, and social withdrawal i.e., 20, 17, 27, 20, 19%, and 35.5%, respectively. Inversely, self-control in social relations, and academic, emotional, physical, and family self-concept fell to 16, 32, 27, 22%, and 37%, respectively. The interrelationship among these variables and the implications of these results for interventions are discussed.